Analisis Perbandingan Operasional Warehouse Sebelum dan Setelah Penerapan ISO 9001 : 2000 di PT. CASMI - Ismulyana Djan; Abdulah . (STIE Binaniaga, 2007)
There are many ways available in implementing management strategy in a company, one of them is by improving quality and work procedure systems through the use of Management Standardization. There are a number of standardizations both international (such as ISO) and national (like SNI) are in use at the moment. Both standardizations are based on a system from an independent body that entitles to give a certificate to a company or an institution that has applied the standardization system. In order to get the precise and accurate research results, the process of data collection and analysis should be done in a scope that carefully planned by comparing data in the operational warehouse before and after the application of ISO to get the final decision. The aspects of the operational research are: the target and actual data of incoming and out coming products, during a certain period prior to the ISO application i.e. 2002, 2003, 2004 and the period when ISO was executed in 2005, 2006 and 2007. There was a significant rise from the amount of target and actual incoming and out coming products handled in the warehouse. This was due to the influence of ISO application particularly on the action, improvement and prevention aspects that consistently applied. While from the actual out coming products there was no big change cause by other factors. Having done the research we hope this study will give new information for all parties especially for marketing department where the strategic steps are taken to maintain the continuous operation of the company as well as in other department particularly the warehouse.